Determining The Food and Nutrition Literacy Status of Universıty Students (Turkey Health Literacy Journal, 2025)
Background and Objectives: Food literacy is a multidimensional concept that encompasses the knowledge, skills and motivation to effectively access and use nutrition information. Improving food literacy can promote healthier eating habits, reduce the risk of diet-related diseases, and improve the overall well-being of university students. This study aims to assess the level of food and nutrition literacy among university students. Material and Methods: The population of the study consisted of students of xxx University, while the sample consisted of 560 students. The data of the study were collected using socio-demographic information form and Food and Nutrition Literacy Scale (FNL). Descriptive statistics, Mann-Whitney U test or Kruskal-Wall test were used to analyse the data. Results: It was found that women scored higher on the attitude dimension, that the mean score on the knowledge and behaviour dimension increased with increasing age, that the score of the students of the Vocational School of Health Services was lower than that of the other departments on the knowledge and behaviour dimension, and that the scores on the knowledge and behaviour dimension increased with increasing class. It was found that the behavioural dimension of those who received nutrition support was higher than those who did not, and the mean score of those who received nutrition education was higher in the knowledge and behaviour dimension (p<0.05). Conclusion: It was found that students did not have an adequate level of food and nutrition literacy and that gender, age, class and education influenced this level. In line with these findings, it is recommended that training programmes aimed at raising awareness of healthy eating should be expanded in universities and that sustainable food policies should be developed to enable students to make informed food choices.